2008
DOI: 10.1021/la703981q
|View full text |Cite
|
Sign up to set email alerts
|

Nematic Pancakes Revisited

Abstract: The spontaneous spreading of the 5CB nematic liquid crystal on solid substrates has been extensively studied in the last years both at the microscopic(1-4) and macroscopic(5-6) scales. The remarkable feature at the microscopic scale is the presence of a discontinuity in the thickness profile of the films. On the other hand, the spreading dynamics of macroscopic drops is quite specific. The drop first spreads like a simple liquid, and then progressively faster, while a remarkable bell-shaped profile develops at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(80 citation statements)
references
References 34 publications
5
74
1
Order By: Relevance
“…As such, it represents a significant advance of the type recently called for by Delabre and co-workers [7]. In the systems we investigated, the theory appears able to describe the discontinuous structural transition between the two main hybrid-anchored states, although the critical thickness is overestimated.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…As such, it represents a significant advance of the type recently called for by Delabre and co-workers [7]. In the systems we investigated, the theory appears able to describe the discontinuous structural transition between the two main hybrid-anchored states, although the critical thickness is overestimated.…”
Section: Discussionmentioning
confidence: 67%
“…This was initially interpreted in terms of competition between elasticity and van der Waals forces [5], though an alternative explanation based on fluctuation-induced interactions was also proposed [6]. Very recently, a more comprehensive experimental study of such systems has been undertaken [7], which 2 concluded that neither of these theoretical descriptions is robust for film thicknesses below 50 nm. Instead,the authors of [7] called for a theoretical description capable of recognising the molecular structure within such film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thick films are expected to show a simple and homogeneous structure in the layer plane (defining a 2D c director sketched in Fig. 1B) but when the thickness h decreases to a fraction of microns, a spatial xy modulation of the director field and periodic domain patterns, due to an elastic instability, are observed (22,23). We checked that the particle-free films deposited on PVA/water behave similarly.…”
Section: Significancementioning
confidence: 98%
“…Stripe patterns in achiral centrosymmetric materials have been observed in a rich variety of physical systems: magnetic films, [2] freestanding smectic films, [3][4][5] ultrathin prefreezing smectic, [6] nematic films. [7][8][9][10][11] Nematic liquid crystals are liquids formed by anisometric molecules. The intermolecular forces acting among the molecules are such to induce a parallel orientation of the molecular long axes.…”
Section: Introductionmentioning
confidence: 99%